A novel highly selective ratiometric fluorescent sensor for relay recognition of Zn2+ and H2PO4−. Issue 4 (24th January 2018) - Du, Kui; Niu, Shizhen; Chen, Xinzhi; Zhang, Pengfei
Graphical abstract: Abstract: A novel fluorescent sensor (AQTF1 ) based on the N-(quinolin-8-yl) tetrahydrofuran-2-carboxamide was designed and synthesized. This new sensor demonstrated high selectivity for the Zn 2+ without the interference from Cd 2+ . The detection limit of this probe was calculated to be 10.8 nM for Zn 2+ . The in situ preparedAQTF1 -Zn 2+ complex was used for detection of H2 PO4 − and displayed good selectivity from the common anions. Furthermore, theAQTF1 displayed good ratiometric response for the relay recognition for Zn 2+ and H2 PO4 − .